Collisions of Animals With Road Vehicles in Traffic in the Czech Republic in Connection with Tourism – Analyses of Causes and Prevention - Petr Šmíd; Emílie Pecharová; Dagmar Škodová Parmová (DETUROPE)
The paper analyses the collisions of animals with means of transport in road traffic in the entire territory of the Czech Republic in connection with tourism. The collisions were evaluated for the period from 2007 to 2016 under the different conditions in which they occurred, for example, season, time of day, weather conditions, visibility and the like. The development of the number of accidents in individual periods and the scope of damage in relation to the collisions are analysed in such a manner as to allow for comparison of any financial resources spent on prevention with damage that has already occurred. The result is that highest number of accidents was recorded in 2016, the lowest in 2009. After 2008, the rate of accidents involving collisions with animals had a declining trend, but rapidly increased again from 2010. Another finding is that highest damage to property occurred in 2016 in the amount of €13,974,886, while the least was in 2009 in the amount of €4,225,879. If we focus on the health and safety of people, which is the highest priority of the research, we ascertained that in the period in question a total of 923 people were injured, of whom 5 people unfortunately died of their injurie and other research results are shown in the text.